Respuesta :
Hello there!
The answer is 17
-----------------------------------------------------------------------------------------------------
Explanation/Work:
42 + 4 = 29 + ?
Step 1: Simplify both sides of the equation.
42 + 4 = 29 + ?
(42 + 4) = ? + 29 (Combine Like Terms)
46 = ? + 29
46 = ? + 29
Step 2: Flip the equation.
? + 29 = 46
Step 3: Subtract 29 from both sides.
? + 29 = 46
-29 -29
? = 17
I hope I helped!
Let me know if you need anything else!
~ Zoe
The answer is 17
-----------------------------------------------------------------------------------------------------
Explanation/Work:
42 + 4 = 29 + ?
Step 1: Simplify both sides of the equation.
42 + 4 = 29 + ?
(42 + 4) = ? + 29 (Combine Like Terms)
46 = ? + 29
46 = ? + 29
Step 2: Flip the equation.
? + 29 = 46
Step 3: Subtract 29 from both sides.
? + 29 = 46
-29 -29
? = 17
I hope I helped!
Let me know if you need anything else!
~ Zoe